2019
DOI: 10.1038/s41598-019-49280-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous spermidine on floral induction, endogenous polyamine and hormone production, and expression of related genes in ‘Fuji’ apple (Malus domestica Borkh.)

Abstract: Flower bud formation in ‘Fuji’ apple ( Malus domestica Borkh .) is difficult, which severely constrains commercial production. Spermidine (Spd) plays an important role in floral induction, but the mechanism of its action is incompletely understood. To investigate the effect of Spd on flowering, 6-year-old ‘Fuji’ apple trees were treated with 1 × 10 −5 mol L −1 Spd to study the responses of polyamines [putrescine (Put), Spd and spermine (Spm)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…ADC2 -overexpressing transgenic plants exhibited a reduction in both the contents of GA 1, 4, 9 contents, and in the expression levels of the GA20ox1 , GA3ox1 and GA3ox3 transcripts [63], suggesting that PUT accumulation represses GA synthesis. SPD treatment decreased GA 3 content, and GA3ox expression in apple terminal buds during floral induction [4]. However, on the other hand, an increased content of GAs was observed in PA-treated plants under drought conditions in creeping bentgrass [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADC2 -overexpressing transgenic plants exhibited a reduction in both the contents of GA 1, 4, 9 contents, and in the expression levels of the GA20ox1 , GA3ox1 and GA3ox3 transcripts [63], suggesting that PUT accumulation represses GA synthesis. SPD treatment decreased GA 3 content, and GA3ox expression in apple terminal buds during floral induction [4]. However, on the other hand, an increased content of GAs was observed in PA-treated plants under drought conditions in creeping bentgrass [64].…”
Section: Discussionmentioning
confidence: 99%
“…The total and individual PAs levels vary depending on the plant species, the organ and on the developmental stage; furthermore, their metabolism is dynamic, due to the polyamine cycle [3]. Experiments on treatments with both PAs and PA synthesis inhibitors revealed the role of PAs in e.g., flower induction [4], embryogenesis [5], regulation of nucleic acid synthesis and protein translation, development of organelles [6], and senescence [7], and numerous studies have been published on the relationship between the enhanced synthesis of PAs and the level of a stress tolerance [8,9,10]. A positive role of the early stress-induced activation or the overexpressing of certain PA-biosynthesis genes has also been proved (arginine decarboxylase: ADC , spermidine synthase: SPDS and spermine synthase: SPMS ) [11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In plants, putrescine, spermidine, and spermine play a role in growth, disease resistance, and reproduction. It was found that the application of spermidine in vitro during flower bud differentiation can significantly improve the flowering rate of 'Fuji' apple [30]. In Arabidopsis, it was found that the addition of a low concentration of spermidine in the pollen medium could promote the elongation of the pollen tube [9].…”
Section: Discussionmentioning
confidence: 99%
“…There is a specific pattern of gibberellins concentrations and polyamines that induce the differentiation of vegetative buds into floral buds being that the crosstalk between polyamines and gibberellins can affect floral differentiation (Anwar et al, 2015;Qin et al, 2019;Kamiab et al, 2020). Nambeesan et al (2019) observed that polyamines, especially spermidine, interfere in the floral identity and development of tomato fruits affecting the GA metabolism and signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines and gibberellins participate in several other biosynthetic / catabolic pathways, with specific distribution patterns in the tissues (Chen et al, 2019). The relation between gibberellin and polyamines reflects in flower induction (Qin et al, 2019;Nambeesan et al, 2019;Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%